Assessing the Impact of Closed and Open Kinetic Chain Hydrotherapy on Vertical Ground Reaction Force, Rate of Loading, Lumbo-Pelvic Stability, Pain Intensity, and Kinesiophobia in Men with Non-Specific Chronic Low Back Pain: A Randomized Clinical Trial - Hossien Ashoury; Ali Yalfani; Mahdi Arjipour (Journal of Rehabilitation Sciences and Research)
Background: Chronic non-specific low back pain (CNSLBP) is a leading cause of work absenteeism and increased dependence on healthcare services and insurance. Despite its prevalence, limited research has explored the effects of open and closed kinetic chain (O/CKC) exercises performed in water on improving CNSLBP-related outcomes. This study aimed to assess the impact of hydrotherapy-based closed and open kinetic chain exercises on lumbo-pelvic stability, pain intensity, kinesiophobia, rate of loading (ROL), and vertical ground reaction force (vGRF) in men with CNSLBP. Methods: The double-blind randomized controlled trial was designed with a pre-post test in men aged 40–60 (48.10 ± 5.97) with CNSLBP. Patients were randomly assigned to two hydrotherapy groups—CKCE and OKCE—and a control group. Pain intensity, kinesiophobia, lumbo-pelvic stability (LPS), rate of loading (ROL), and vertical ground reaction force (vGRF) were measured using the visual analog scale, Tampa Kinesiophobia Scale, biofeedback pressure device, and plantar pressure device. The intervention groups performed prescribed exercises for eight weeks, with three sessions per week. Covariance analysis was used to compare group differences. Results: In the comparison within the OKCE and CKCE groups, significant differences were observed between the pre- and post-intervention measurements (p < 0.05). Moreover, statistically significant differences were found in pain (p = 0.001) and kinesiophobia scores (p = 0.001), both with a large effect size. Additionally, noteworthy differences were noted in vGRF (p = 0.003), ROL (p = 0.012), and LPS (p = 0.022). Conclusion: The study results indicate that hydrotherapy exercises involving open and closed kinetic chains benefit individuals with CNSLBP. It is recommended that healthcare professionals, including physicians, physiotherapists, and occupational therapists, incorporate these exercises into comprehensive rehabilitation programs for such patients.